صور العنف الأسري ضد المرأة كما عكسته الدراما في القنوات الفضائية السورية خلال شهر رمضان المبارك 2012م دراسة ميدانية على عينة من طالبات كلية الآداب في جامعة تشرين (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
نلاحظ اليوم أن العولمة بأدواتها المختلفة عملت وتعمل على نشر الفوضى والعنف وهدر الانتماء من خلال مشروعها الموجه نحو المرأة والشباب والطفولة, إذ أنها تعمل على سلخهم عن هويتهم وانتماءاتهم واتباعهم باقتصاد السوق فوق الوطني الذي يلغي الوطن ويُحل محله رقم الحساب المصرفي وبطاقة الائتمان , ويعمل على تشييء الإنسان منا وتسليعه ليغدو إنساناً مدجّناً في قوالب جامدة تزيد من هدر كيانه وتحوله إلى أداة تفعل به العولمة فعلها المنشود . وما صورة المرأة الجسد الفاتن أداة الإعلانات , وترويج مختلف السلع الاستهلاكية عبر فتنة الجسد المشتهى إلا نوعاً من تحويل المرأة إلى اسطورة متعددة الدلالات في ( الإلهاء ورضاعة التسلية والعنف والانحراف في الإثارة المادية وغيرها ... ) فهل أسهمت محطاتنا التلفزيونية في تكريس هذه الصورة ؟ أم هل عملت الدراما على تغيير هذه الصورة والحد من ظاهرة العنف الأسري الممارس ؟! ما هي التوصيات والاقتراحات التي يمكن أن تغني هذا البحث وتقدم الحلول الناجعة لظاهرة العنف الأسري ضد المرأة في مجتمعنا ؟ . We can notice nowadays that globalization, with its own variety of means, has worked and is still working to spread chaos and violence and to destroy affiliation through its project oriented against women, youth and childhood. Globalization is trying to uproot their identity and affiliations and subordinate them to the market economy that disregards the sense of nationalism and replace it with a bank account and credit card number. It also works to objectify our humanity and change it into a commodity to change the individual into a domesticated human being in rigid molds, wasting his/her existence and transforming them into a tool. The image of female body is no more than an advertising tool, used for the promotion of various merchandise through focusing on the instinctive sexual aspects. This transforms women into a myth with multiple connotations (distraction and "breastfeeding" entertainment, violence and delinquency, excitement of physical desires, etc). Has TV drama on Syrian TV satellite channels contributed to the promotion of this image? Or has it worked to change this image and reduce the phenomenon of domestic violence actually practised? What are the recommendations and suggestions that can enrich this research and provide solutions regarding the phenomenon of domestic violence against women in our society? .